Investigation of the aqueous salt solutions of some first and second group metals at various pressures - Filiz, Mehmet; Guelen, Jale (ELSEVIER SCIENCE BV, 2008)
In the scope of this study, boiling points of aqueous solutions of NaCl, DCl, CaCl(2), BaCl(2), KNO(3) and Ca(NO(3))(2) salts with salt concentrations between 0.5335 and 6.5935 mol kg(-1) within 21.332-101.325 kPa pressure range have been determined. Duhring diagrams have been plotted for each solution. In cases, where Raoult's law applied to non-dilute solutions, the deviations from these were determined. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Duhring diagrams; aqueous electrolyte solutions; Raoult deviations; BOILING-POINT ELEVATION; VAPOR-PRESSURES; SODIUM-CHLORIDE; THERMODYNAMIC PROPERTIES; MAGNESIUM-NITRATE; TEMPERATURE-RANGE; CALCIUM NITRATE; 323 K; WATER; SULFATE; Thermodynamics; Chemistry; Engineering